Polityka genderowa Unii Europejskiej - geneza i ewolucja - Jastrzębska, Ewa (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2014)
The purpose of this article is to assess the phenomenon of discrimination against women and ways to combat it in the EU. The starting point of consideration is an attempt to define contemporary feminism and to identify the common mani‑ festations of discrimination against women. Set against this background are the institutionalised actions taken in favour of women on a global scale as well as EUs gender policy. It was found that the gap that occurs between gender equality de jure and de facto contributed to the implementation in the EU of the principle of gender mainstreaming (active and visible to the mainstreaming of gender in all strategies, policies and programmes).